Analysis of Big Data Platform Implementation and Operation - Yong Chen; Ang Gao (Dianxin kexue)
Big data is transiting from emerging technology to large-scale production operations. The implementation and operation of shared infrastructure platform becomes key factors for successfully deploying big data. Analysis was made for infrastructure planning, integration and operation. Methodology was given for implementing a better shared platform for large scale big data application.